1993
DOI: 10.2307/353333
|View full text |Cite
|
Sign up to set email alerts
|

American Family Decline, 1960-1990: A Review and Appraisal

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. National Council on Family Relations is collaborating with JSTOR to digitize, preserve and extend access to Journal of Marriage and Family. A Review and AppraisalContrary to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
179
0
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(205 citation statements)
references
References 61 publications
2
179
0
14
Order By: Relevance
“…In 1987 a substantial correction was made; also during 1993and during 2000and during -2004and during . The 2000and during -2004 decline of the S&P500 P/E ratio in the order of around 50 percent is very significant in terms of the course of economic activity.…”
Section: Ssa Function Of Financial Stabilitymentioning
confidence: 99%
“…In 1987 a substantial correction was made; also during 1993and during 2000and during -2004and during . The 2000and during -2004 decline of the S&P500 P/E ratio in the order of around 50 percent is very significant in terms of the course of economic activity.…”
Section: Ssa Function Of Financial Stabilitymentioning
confidence: 99%
“…Unconditional, in-group helpfulness is modeled for children from infancy (MOGHADDAM, TAYLOR and WRIGHT 1993). Because of this intergenerational support that is expected and prized in collectivist cultures, it has been suggested that these cultures buttress marriage (TRIANDIS, 1995;BRISLIN 2000;POPENOE 1993).…”
Section: Individualist and Collectivist Culturesmentioning
confidence: 99%
“…Marriage cohort tables show that divorce increased from 2% after five years of marriage for couples married in 1960 to about 13% for couples married in the early 1990s (Kalmijn, De Graaf, & Poortman, 2004). Popenoe (1993) contends that this increase has major consequences, changing the structure and further reducing the functions of families, and divorce has been found to have an adverse effect on parent-child relationships (Aquilino, 1994;Eggebeen, 1992). Specifically, these studies suggest that divorce results in less contact and instrumental and emotional support between the divorced parent and the child.…”
Section: Consequences Of Opportunitiesmentioning
confidence: 99%